THE TECHNOLOGY OF CREATING A THEMATIC COMPOSITION: INTERPRETING COMPOSITIONAL ISSUES IN PAINTINGS - Sobirova Gulchekhrakhan Shokirjonovna; Abdullayev Oktamjon Ergashevich (Galaxy International Interdisciplinary Research Journal, 2024)
This scientific article delves into the technology behind creating a thematic composition based on the interpretation of compositional issues in a painting. Compositional aspects in paintings play a critical role in conveying the theme and message to the viewers. By understanding the techniques and principles employed in composing paintings, artists and art enthusiasts can elevate their ability to create thematic compositions that effectively communicate ideas. This article explores the technological advancements and methodologies employed to analyze, interpret, and subsequently create harmonious thematic compositions inspired by paintings.